2017
DOI: 10.1097/olq.0000000000000590
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone and Internet Use Mostly for Sex-Seeking and Associations With Sexually Transmitted Infections and Sample Characteristics Among Black/African American and Hispanic/Latino Men Who Have Sex With Men in 3 US Cities

Abstract: Background Men who have sex with men (MSM) have a relatively high prevalence of sexually transmitted infections (STIs). This study examines the association of self-reported STIs and use of mobile phones and/or computer-based Internet to meet sexual partners among black and Hispanic/Latino MSM in the U.S. Methods Black and Hispanic/Latino MSM (N=853) were recruited from three U.S. cities (Chicago, IL, Kansas City, MO, and Fort Lauderdale, FL) via online and community outreach. Men completed a computer-assiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…More than half of these studies ( n = 15/25, 60.0%) recruited app-users aged were 18 or above years of age [ 5 , 13 , 21 27 , 29 , 32 , 34 , 36 38 , 41 , 43 45 ], and showed a predominance of young adults (18 to 30 years old; n = 8/15, 53%) [ 5 , 13 , 21 , 22 , 25 , 36 , 38 , 41 , 43 45 ]. According to the available data, 4427 (54.2%) app-users were white, 5754 (78.2%) were gay-identified and 6420 (71.3%) had at least college education.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…More than half of these studies ( n = 15/25, 60.0%) recruited app-users aged were 18 or above years of age [ 5 , 13 , 21 27 , 29 , 32 , 34 , 36 38 , 41 , 43 45 ], and showed a predominance of young adults (18 to 30 years old; n = 8/15, 53%) [ 5 , 13 , 21 , 22 , 25 , 36 , 38 , 41 , 43 45 ]. According to the available data, 4427 (54.2%) app-users were white, 5754 (78.2%) were gay-identified and 6420 (71.3%) had at least college education.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies assessed self-reported HIV diagnosis [ 3 , 4 , 6 , 23 , 27 , 32 , 33 , 38 ]. Since we found medium heterogeneity (I 2 = 45%, P heterogeneity = 0.08) among these studies, a random-effects model was used to pool the OR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of sexualized venues such as brothels, bathhouses and sex-seeking social media create specific environments where HIV/STI can be efficiently spread [43,44]. These physical spaces and/or online connections [45][46][47] may lead to rapid partner turnover, increasing the likelihood of HIV/STI transmission. In socially marginalized populations with high HIV/STI prevalence, the limited choice of new partners leads to increased risk through assortative mixing.…”
mentioning
confidence: 99%